Implementation of Coaching Strategy as a Capacity Strengthening for Madrasah Principals in Conducting Evaluations - R, Abdul Rahman; Saud, Syukur; Badriah, Badriah; Saud, Chaerul Fadlan; Syuraedah, Rezky (Phonologie : Journal of Language and Literature, 2024)
Abstract. The purpose of this study is to determine the ability of the Madrasah principal in carrying out his duties as the person in charge of the Madrasah in conducting distance learning evaluations. The evaluation process that should be carried out by the Madrasah principal even though it is in the distance category must still be maximized, but sometimes the process cannot be maximized because it is considered new and in the adjustment stage. One of the reasons for this study is to improve the ability of the Madrasah principal as the person in charge of the Madrasah to conduct evaluations through Coaching Strategy. This study was conducted using the Action Research research method involving three Madrasah principals supervised by researchers to obtain accurate data related to the ability of the Madrasah Principal to conduct evaluations. Research data were collected through observation, interviews, filling out questionnaires, and document assessments. Research data were analyzed through data reduction, data presentation, and verification, equipped with quantitative data descriptions of the results of the process assessment and document assessment. The assessment results showed an average score of 72%, including the "good" category and meeting the performance indicators (> 70%). The assessment results in Cycle-II increased by 10% compared to the average score in Cycle-I, which was 72%. Participants generally realized that in order to carry out an evaluation, they must first prepare a program correctly.Keyword: Implementation, Coaching, Strategy, Madrasah, conductive Evaluation